2020
DOI: 10.3390/metabo10060225
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Annotation by Combination of UHPLC-HRMS (MS), Molecular Networking, and Retention Time Prediction: Application to a Lipidomic Study of In Vitro Models of Dry Eye Disease

Abstract: Annotation of lipids in untargeted lipidomic analysis remains challenging and a systematic approach needs to be developed to organize important datasets with the help of bioinformatic tools. For this purpose, we combined tandem mass spectrometry-based molecular networking with retention time (tR) prediction to annotate phospholipid and sphingolipid species. Sixty-five standard compounds were used to establish the fragmentation rules of each lipid class studied and to define the parameters governing their chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 60 publications
2
21
0
Order By: Relevance
“…Through analyzing human corneal epithelial cells (CEC) exposed to hyperosmosis stress (HS) and control status, more than 150 unique phospholipids and sphingolipids were annotated and this lipid histochemical study highlighted the relationship between lipid changes in corneal cells exposed to HS and inflammatory responses. 4 Besides, in a previous study, it was found that HS would lead to an excessive reactive oxygen species release and lead to decreased autophagy and decreased cell activity in DED. 5 Protection of CEC in the pathological status would help in the management of DED and this research approach provided us various potential therapies for DED.…”
Section: Introductionmentioning
confidence: 95%
“…Through analyzing human corneal epithelial cells (CEC) exposed to hyperosmosis stress (HS) and control status, more than 150 unique phospholipids and sphingolipids were annotated and this lipid histochemical study highlighted the relationship between lipid changes in corneal cells exposed to HS and inflammatory responses. 4 Besides, in a previous study, it was found that HS would lead to an excessive reactive oxygen species release and lead to decreased autophagy and decreased cell activity in DED. 5 Protection of CEC in the pathological status would help in the management of DED and this research approach provided us various potential therapies for DED.…”
Section: Introductionmentioning
confidence: 95%
“…The members of this molecular family are key mediators in intercellular and intracellular processes in both inflammatory processes and cell death phenomena [86,87]. Interestingly, these bioactive lipids and their modulation were also described in studies of an in vitro DED model [88,89]. This metabolic involvement is supported by the identification of several enzymes.…”
Section: Discussionmentioning
confidence: 87%
“…Chromatographic separation was achieved on an Acquity ® CSH C18 column (100 mm × 2.1 mm, 1.7 μm). UHPLC-HRMS data acquisition and analysis were adapted from a previously described protocol [ 17 ]. Data dependent acquisition was performed to provide tandem mass spectra of the five most intense ions detected on a first mass spectrum.…”
Section: Methodsmentioning
confidence: 99%